Histologic, immunohistochemical, and scanning electron microscopic comparison of pre‐iridal monocellular and fibrovascular membranes in normal and glaucomatous canine globes. (27th April 2021) - Bedos, Leila; Grahn, Bruce H.; Philibert, Helene; Campbell, John; Sandmeyer, Lynne
Abstract: Objectives: (i) To evaluate immunohistochemical labeling of pre‐iridal monocellular and fibrovascular membranes and (ii) describe the light and scanning electron microscopic (SEM) characteristics of these membranes in glaucomatous and normal/control canine globes. Materials and methods: All globes were evaluated with light microscopy. Immunohistochemical labeling for CD18, Smooth muscle actin (SMA), and CD117 was completed on 40 canine globes with congenital/anterior segment dysgenesis‐associated glaucoma ( n  = 10), primary/goniodysgenesis‐associated glaucoma ( n  = 10), secondary glaucoma ( n  = 10), and normal/control globes ( n  = 10). SEM was completed on 10 globes: 5 with monocellular membranes, 3 with fibrovascular membranes, and 2 without a histologically detectable membrane. Results: Monocellular membranes were detected in all normal/control globes with light microscopy and appeared to be morphologically very similar to those in diseased globes. CD18 labeling was detected in 9/10 monocellular membranes in normal/control globes, 15/23 monocellular, and 7/8 fibrovascular membranes in globes with glaucoma. SMA and CD117 labeling was not detected in monocellular membranes of normal/control globes. SMA was expressed in 10/23 monocellular and 7/8 fibrovascular membranes of glaucomatous globes. CD117 was expressed in 7/23 monocellular and 5/8 fibrovascular membranes of glaucomatous globes. SEM of monocellular membranes revealed a continuous sheet of mostly spindle cells and few individual round cells that extended over the anterior iris face in normal/control and all glaucomatous globes. Conclusion: Pre‐iridal monocellular membranes are a normal component of the anterior iris surface, and CD18 immunoreactivity suggests some cells within these are of leukocytic origin. SMA and CD117 labeling of monocellular membranes in glaucomatous, but not normal/control globes, suggest metaplastic cellular change secondary to intraocular pathology related to glaucoma.